Treatment of the chronic mental patient: issues and implications - O'Dea, Patricia Ann Margaret (Department of Psychology, 2016)
The aim of this study is to clarify the unique needs of the chronic mental patient, and draw implications therefrom for the design of comprehensive and effective systems of continuous care. The history of treatment for mental patients in the western industrialized world is reviewed, with special emphasis on the ethical, legal and socio-cultural background to the deinstitutionalization movement, and the development of new models of caring for the chronic mental patient. Recent attempts to humanize mental health care are examined for guidelines to more successful planning in the future.